2022
DOI: 10.3201/eid2805.212488
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Relative Abundance of 2 SARS-CoV-2 Variants through Wastewater Surveillance at 2 Large Metropolitan Sites, United States

Abstract: B y November 2021, the coronavirus disease (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), had claimed >5 million lives worldwide, including >700,000 in the United States (1-3). Since its emergence in late 2019, SARS-CoV-2 has mutated, resulting in some variants categorized by the World Health Organization as variants of concern (VOCs). VOCs have evidence of potential increased infectiousness, immune evasion, and clinical severity, and they have spread globally. Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The load of SARS-CoV-2 viral RNA in wastewater can be used to follow the trajectory of COVID-19 infections in the cities studied (Fig. S1) ( Crits-Christoph et al, 2021 ; Arts et al, 2022 ; Xie et al, 2022 ; Yu et al, 2022 ). Delta became the only VOC in the cities studied after it had replaced the Alpha VOC in June 2021 ( Xie et al, 2022 ), which occurred before the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The load of SARS-CoV-2 viral RNA in wastewater can be used to follow the trajectory of COVID-19 infections in the cities studied (Fig. S1) ( Crits-Christoph et al, 2021 ; Arts et al, 2022 ; Xie et al, 2022 ; Yu et al, 2022 ). Delta became the only VOC in the cities studied after it had replaced the Alpha VOC in June 2021 ( Xie et al, 2022 ), which occurred before the current study.…”
Section: Resultsmentioning
confidence: 99%
“…The emerging and the dominant, circulating VOCs in each community were monitored cost-effectively, with limited biases by wastewater surveillance ( Ai et al, 2021 ). Wastewater surveillance has been a useful tool for monitoring overall SARS-CoV-2 RNA and understanding the specific VOCs dominating each community ( Yu et al, 2022 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The most widely adopted WBE as of today is RT-qPCR/ddPCR/dPCR where the level of detected SARS-CoV-2 could be reported 32,33 . Further, with the applications of variant-specific assays, the quantification of a variant’s presence has also been realized 34 . While quantification-based methods provide useful information for existing SARS-CoV-2 variants that are already known to be circulating in a community, whole genome sequencing of SARS-CoV-2 from wastewater is attractive because it not only provides higher resolution of the known circulating variants, but also enables broad identification of novel mutations within the context of the whole genome, therefore contributes to understanding the viral evolution and/or transmission within the sewersheds.…”
Section: Discussionmentioning
confidence: 99%
“… 5 8 A number of studies have illustrated that circulating or novel variants can be identified in wastewater using RT-PCR assays that target a characteristic variant mutation 9 11 and by sequencing SARS-CoV-2. 12 , 13 We previously developed targeted RT-PCR assays for characteristic mutations in Alpha, Mu, Lambda, Delta, and Omicron BA.1 and showed that the concentrations of these mutations, normalized by a pan-SARS-CoV-2 nucleocapsid (N) gene target, are strongly correlated to the fraction of clinical specimens classified as the associated variant 10 , 14 at two publicly owned treatment works (POTWs). Here, we extend that previous work by developing and testing two new assays, one that targets characteristic mutations in the BA.2 sublineage of Omicron and another that targets a set of mutations present in both BA.1 and BA.2.…”
Section: Introductionmentioning
confidence: 99%
“…It contains feces, urine, sputum, mucus, blood, vomitus, and any other excretion that goes down a drain into the sewer network. Global investigations have illustrated that SARS-CoV-2 RNA concentrations, whether measured by RT-QPCR or digital RT-PCR or in the liquid or solid phase of wastewater, correlate well with laboratory-confirmed incident COVID-19 cases in the associated sewersheds. A number of studies have illustrated that circulating or novel variants can be identified in wastewater using RT-PCR assays that target a characteristic variant mutation and by sequencing SARS-CoV-2. , We previously developed targeted RT-PCR assays for characteristic mutations in Alpha, Mu, Lambda, Delta, and Omicron BA.1 and showed that the concentrations of these mutations, normalized by a pan-SARS-CoV-2 nucleocapsid (N) gene target, are strongly correlated to the fraction of clinical specimens classified as the associated variant , at two publicly owned treatment works (POTWs). Here, we extend that previous work by developing and testing two new assays, one that targets characteristic mutations in the BA.2 sublineage of Omicron and another that targets a set of mutations present in both BA.1 and BA.2.…”
Section: Introductionmentioning
confidence: 99%